2002
DOI: 10.1002/etc.5620211118
|View full text |Cite
|
Sign up to set email alerts
|

17α‐ethynylestradiol‐induced vitellogenin gene transcription quantified in livers of adult males, larvae, and gills of fathead minnows (Pimephales promelas)

Abstract: We have applied a method for quantifying relative levels of messenger RNA (mRNA) transcription to assess chemically induced gene expression in fathead minnows (Pimephales promelas). Synthetic oligonucleotides designed for the fathead minnow vitellogenin gene transcription product were used in a reverse transcription polymerase chain reaction (RT-PCR) protocol. This sensitive and rapid strategy detected vitellogenin gene transcription in livers of male fathead minnows exposed to concentrations as low as 2 ng/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 52 publications
2
28
0
1
Order By: Relevance
“…The binding affinity of E2 to fhmER and rbtER essentially was the same, with mean IC50s of 6.7 Ϯ 1.3 nM (n ϭ 8) and 6.6 Ϯ 2.4 nM (n ϭ 31), respectively. In addition, numerous studies have shown that EE2 induces vitellogenin in both fathead minnows [23,[25][26][27][28] and rainbow trout [29][30][31]. The RBAs for DES, EE2, and E1 determined in this study were within fivefold of one another and are comparable with the values reported by Tollefsen et al (Table 1 [15]).…”
Section: Relative Binding Affinitiessupporting
confidence: 88%
“…The binding affinity of E2 to fhmER and rbtER essentially was the same, with mean IC50s of 6.7 Ϯ 1.3 nM (n ϭ 8) and 6.6 Ϯ 2.4 nM (n ϭ 31), respectively. In addition, numerous studies have shown that EE2 induces vitellogenin in both fathead minnows [23,[25][26][27][28] and rainbow trout [29][30][31]. The RBAs for DES, EE2, and E1 determined in this study were within fivefold of one another and are comparable with the values reported by Tollefsen et al (Table 1 [15]).…”
Section: Relative Binding Affinitiessupporting
confidence: 88%
“…Vitellogenin mRNA analysis was performed using the method of Lattier et al [20], with modifications. The quality of the RNA was assessed and quantified spectrophotometrically with absorbance measurements at 260 nm with a Molecular Devices Spectramax M5e reader.…”
Section: Vitellogenin Mrna Analysismentioning
confidence: 99%
“…This makes comparison to other studies that had exposure concentrations <10 or >10 ng/L possible. Fathead minnow have failed development of secondary sex characteristics, altered mating behaviour, intersex and induced VTG in males at 1-5 ng/L EE 2 (Länge et al, 2001;Lattier et al, 2002;Parrott and Blunt, 2005); Japanese medaka display intersex and reduced copulations at 2-10 ng/L EE 2 (Balch et al, 2004); and zebrafish have reduced spawning, fertilization, intersex and GSI at 5-10 ng/L EE 2 (Van den Belt et al, 2001Belt et al, , 2002Nash et al, 2004). In contrast to freshwater species, in which effects are observed at concentrations 610 ng/L EE 2 , sheepshead minnow have reduced reproductive success at EE 2 between 20 and 200 ng/L (Zillioux et al, 2001) while mummichog have altered steroid synthesis, VTG induction, reproductive success and sex differentiation at >10 ng/L EE 2 (MacLatchy et al, 2003;Peters et al, 2007;this study).…”
Section: Tablementioning
confidence: 99%